2008
DOI: 10.1002/pmic.200700249
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of human osteoarthritic chondrocytes reveals protein changes in stress and glycolysis

Abstract: Osteoarthritis (OA) is characterized by cartilage degradation. The chondrocyte is the only cell type present in mature cartilage, and it is important in the control of cartilage integrity. The aim of this study was to analyze, by a proteomic approach, the changes that are characteristic of OA chondrocytes, and to identify new OA-related proteins. Chondrocytes were isolated from the cartilage of ten OA patients undergoing joint replacement and ten donors with no history of joint disease. Whole-cell proteins wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
90
0
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 111 publications
(107 citation statements)
references
References 32 publications
12
90
0
5
Order By: Relevance
“…Proteomic analysis of normal and OA chondrocytes has revealed changes in stress-related proteins (Ruiz-Romero et al 2008). Yamasaki et al (2006) reported resistance to ER stress-induced apoptosis in rheumatoid arthritic synovial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Proteomic analysis of normal and OA chondrocytes has revealed changes in stress-related proteins (Ruiz-Romero et al 2008). Yamasaki et al (2006) reported resistance to ER stress-induced apoptosis in rheumatoid arthritic synovial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Whole cell extracts were collected 48 h after CS addition, according to a protocol previously set up by our group (11,16). These samples were then subjected to a six-plex two-dimensional DIGE analysis, resulting in three individual images from each gel (each one corresponding to Cy2-, Cy3-, and Cy5-labeled samples).…”
Section: Analysis Of the Effect Of Different Cs Compounds On Chondrocmentioning
confidence: 99%
“…Nine chondrocyte pellets from nine different donors of each group were mixed to form a "mixed pool." 12,13 Pooled mixture was solubilized by vortex and 1 h incubation with gentle agitation in 500 L of an IEF-compatible lysis buffer containing 8.4 M urea, 2.4 M thiourea, 5% CHAPS, 1% carrier ampholytes (IPG buffer pH 3-10 nonlinear (NL), Amersham Biosciences, Uppsala, Sweden), 0.4% Triton X-100, and 2 mM DTT. For protein quantification, 10 L of the protein extract was diluted 10× with water and precipitated for at least 1 h with 0.02% sodium deoxycholate and 10% TCA.…”
Section: Protein Sample Preparationmentioning
confidence: 99%